ОНКОЛОГИК БЕМОРЛАРДА КАСАЛЛИКНИНГ ИЖТИМОИЙ ТАЪСИРИНИ СУБЪЕКТИВ БАҲОЛАШ МАСАЛАСИНИНГ МУҲИМЛИГИ - Уразбаева, Д.А. (SCIENCE and SOCIETY, 2019)
In the article the author analyzed the problem of the need for an experimental study of the subjective characteristics of the social influence on cancer patients.
Keywords: psychology; psychooncology; patient; attitude towards a disease; personality